2021
DOI: 10.1108/rpj-03-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Casting of complex structures in aluminum using gypsum molds produced via binder jetting

Abstract: Purpose The purpose of present paper is to enlarge the knowledge about the performance of gypsum powder to realize complex molds or cores for aluminum casting. Design/methodology/approach The research was divided into two activities: simple; and complex-part production capability. In the simple-part step, the performance of gypsum powder and the minimum mold thickness that would withstand the casting process. In the complex-part step, the authors first investigated the powder removability as a function of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Additionally, the PCL/BCP surface may stimulate the cell response, and tests have demonstrated that osteoblasts proliferate entirely and differentiate. In 2021, Giorleo et al [ 154 ] used gypsum adhesive to manufacture parts with complex geometries. Tests have shown that the parts produced by this method can withstand the temperature of aluminum castings (720 °C).…”
Section: Powder‐based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the PCL/BCP surface may stimulate the cell response, and tests have demonstrated that osteoblasts proliferate entirely and differentiate. In 2021, Giorleo et al [ 154 ] used gypsum adhesive to manufacture parts with complex geometries. Tests have shown that the parts produced by this method can withstand the temperature of aluminum castings (720 °C).…”
Section: Powder‐based Methodsmentioning
confidence: 99%
“…In 2016, Rouholamin et al [ 264 ] studied the high‐temperature silicon infiltration process, processed TiC ceramics printed by BJ, and obtained Ti 3 SiC 2 ceramics with a bending strength of 293 MPa, a Vickers hardness of 7.2 GPa and a resistivity of 27.8 μΩ cm. In 2021, Giorleo et al [ 154 ] evaluated the possibility of using gypsum adhesive to spray moulds with complex geometries, which confirmed the possibility of using gypsum powder in the aluminum casting process. In 2021, Na et al [ 147 ] researched and optimized the composition of CSA (calcium sulphoaluminate) cement and water glass (Na 2 SiO 3 ) and gypsum jetting 3D printing binder.…”
Section: Powder‐based Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additive manufacturing is an enabling technology of Industry 4.0 thanks to its ability to produce parts characterized by complex structure [1][2]. This ability let the possibility to redesign not only the shape of the part but also to rethink about the chance to do not produce parts as full but with hierarchical structures [3][4]. It is also possible to redesign objects in a single part so that it is avoided the assembly step.…”
Section: Introductionmentioning
confidence: 99%
“…To enable performance validation, such models (prototypes) must be produced using the same material and production process used for full-scale production [5,6]. Today, the main application of RT in conventional production processes is in casting, where it is used in complex-shape and net-shape manufacturing [7,8]. It is also used in injection moulding, to increase process flexibility and reconfigurability [9,10], and in forming, to reduce process costs and production times [11,12].…”
Section: Introductionmentioning
confidence: 99%